Cost-effectiveness of Internet Interventions Compared With Treatment as Usual for People With Mental Disorders: Systematic Review and Meta-analysis of Randomized Controlled Trials - Rohrbach, Pieter J; Dingemans, Alexandra E; Evers, Catharine; Van Furth, Eric F; Spinhoven, Philip; Aardoom, Jiska J; Lähde, Irene; Clemens, Fleur C; Van den Akker-Van Marle, M Elske (Journal of medical Internet research, 2023)
The economic costs of mental disorders for society are huge. Internet-based interventions are often coined as cost-effective alternatives to usual care, but the evidence is mixed. The aim was to review the literature on the cost-effectiveness of internet interventions for mental disorders compared with usual care and to provide an estimate of the monetary benefits of such interventions compared with usual care. A systematic review and meta-analysis of randomized controlled trials was conducted, which included participants with symptoms of mental disorders; investigated a telephone- or internet-based intervention; included a control condition in the form of treatment as usual, psychological placebo, waiting list control, or bibliotherapy; reported outcomes on both quality of life and costs; and included articles published in English. Electronic databases such as PubMed (including MEDLINE), Embase, Emcare, PsycINFO, Web of Science, and the Cochrane Library were used. Data on risk of bias, quality of the economic evaluation, quality-adjusted life years, and costs were extracted from the included studies, and the incremental net benefit was calculated and pooled. The search yielded 6226 abstracts, and 37 studies with 14,946 participants were included. The quality of economic evaluations of the included studies was rated as moderate, and the risk of bias was high. A random-effects approach was maintained. Analyses suggested internet interventions were slightly more effective than usual care in terms of quality-adjusted life years gain (Hedges g=0.052, 95% CI 0.010-0.094; P=.02) and equally expensive (Hedges g=0.002, 95% CI -0.080 to 0.84; P=.96). The pooled incremental net benefit was US $255 (95% CI US $91 to US $419; P=.002), favoring internet interventions over usual care. The perspective of the economic evaluation and targeted mental disorder moderated the results. The findings indicate that the cost-effectiveness of internet interventions for mental disorders compared with a care-as-usual approach is likely, but generalizability to new studies is poor given the substantial heterogeneity. This is the first study in the field of mental health to pool cost-effectiveness outcomes in an aggregate data meta-analysis. PROSPERO CRD42019141659; https://tinyurl.com/3cu99b34.